An Electronic Health Record–Based Intervention to Increase Follow‐Up Office Visits and Decrease Rehospitalization in Older Adults. Issue 5 (29th April 2014) - Gurwitz, Jerry H.; Field, Terry S.; Ogarek, Jessica; Tjia, Jennifer; Cutrona, Sarah L.; Harrold, Leslie R.; Gagne, Shawn J.; Preusse, Peggy; Donovan, Jennifer L.; Kanaan, Abir O.; Reed, George; Garber, Lawrence
<x xml:space="preserve">Abstract</x> Objectives To assess the effect of an electronic health record–based transitional care intervention involving automated alerts to primary care providers and staff when older adults were discharged from the hospital. Design Randomized controlled trial. Setting Large multispecialty group practice. Participants Individuals aged 65 and older discharged from hospital to home. Intervention In addition to notifying primary care providers about the individual's recent discharge, the system provided information about new drugs added during the inpatient stay, warnings about drug–drug interactions, recommendations for dose changes and laboratory monitoring of high‐risk medications, and alerts to the primary care provider's support staff to schedule a posthospitalization office visit. Measurements An outpatient office visit with a primary care provider after discharge and rehospitalization within 30 days after discharge. Results Of the 1, 870 discharges in the intervention group, 27.7% had an office visit with a primary care provider within 7 days of discharge. Of the 1, 791 discharges in the control group, 28.3% had an office visit with a primary care provider within 7 days of discharge. In the intervention group, 18.8% experienced a rehospitalization within the 30‐day period after discharge, compared with 19.9% in the control group. The hazard ratio for an office visit with a primary care physician did not significantly differ between the intervention and control groups. The hazard ratio for rehospitalization in the 30‐day period after hospital discharge in the intervention versus the control group was 0.94 (95% confidence interval = 0.81–1.1). Conclusion This electronic health record–based intervention did not have a significant effect on the timeliness of office visits to primary care providers after hospitalization or risk of rehospitalization.